2012
DOI: 10.1542/peds.2011-2340
|View full text |Cite
|
Sign up to set email alerts
|

Infant Outcomes After Maternal Antiretroviral Exposure in Resource-Limited Settings

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Information on infant safety after exposure to maternal antiretroviral regimens during pregnancy in international clinical trials is lacking. As antiretroviral drugs are released to populations in resource-limited settings through clinical trials, it becomes critical to collect pediatric outcome data. WHAT THIS STUDY ADDS:The study demonstrates the feasibility of reporting infant outcomes following adult antiretroviral trials in developing countries, provides HIV-free infant survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…(31, 32, 35-37) (38-42) Existing research on HIV-exposed infants has suggested that HIV exposure alone may be a risk factor for other infections, particularly in infants born to women with advanced HIV infection, due to genital colonization of pathogens, subclinical chorioamnionitis, and lower protective antibody titers resulting in decreased transfer of passive immunity across the placenta. (43) However, while our infant cohort appeared to be at risk for adverse outcomes from HIV-exposure at baseline, we still found that infants born to CT and/or NG-infected mothers were more likely to have an adverse outcome, irrespective of infant HIV-infection.…”
Section: Discussionmentioning
confidence: 99%
“…(31, 32, 35-37) (38-42) Existing research on HIV-exposed infants has suggested that HIV exposure alone may be a risk factor for other infections, particularly in infants born to women with advanced HIV infection, due to genital colonization of pathogens, subclinical chorioamnionitis, and lower protective antibody titers resulting in decreased transfer of passive immunity across the placenta. (43) However, while our infant cohort appeared to be at risk for adverse outcomes from HIV-exposure at baseline, we still found that infants born to CT and/or NG-infected mothers were more likely to have an adverse outcome, irrespective of infant HIV-infection.…”
Section: Discussionmentioning
confidence: 99%
“…What dictates “substantial” is debatable, but many consider outcomes involving birth weight [6675], congenital defects [76–81], early neurodevelopment [8284] and growth [70,75,8587] as significant, and none of these have demonstrated a clear association with in utero HIV/ARV exposure (Table 3). Even pre-term birth, which has been shown in several studies to be associated with ART [74,8992,95] is still an early infant outcome and would occur and be managed well before adolescence, the time of disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to antenatal AZT has not been found to be associated with SGA in the United States [66] or LBW in Europe [67]. In addition, studies in the United States [72,74] and another multi-country study [75] have reported no associations between antenatal ART and LBW/SGA. A large study in Latin America also did not find risks for LBW when comparing classes of ARVs [73].…”
Section: Discussionmentioning
confidence: 99%
“…The study did not report multivariate analyses adjusting for these or other factors such as maternal regimen or immunosuppression. (33)…”
Section: Intrauterine Growthmentioning
confidence: 99%
“…AZT. (33) Lastly, a secondary analysis of two RCTs in Botswana reported no differences in WAZ or WLZ by 6 months of age in infants exposed to in utero cART vs. AZT prophylaxis. (41)…”
Section: Postnatal Growthmentioning
confidence: 99%